Endovascular brachytherapy with iodine-125 seed strand for extensive portal vein tumor thrombus in patients with hepatocellular carcinoma - Tan, Zhongbao; Wu, Daguang; Guo, Jinhe; Wang, Huanjing; Zhang, Jian (Frontiers in Oncology, 2023)
Objective: The aim of this study is to investigate the feasibility and effectiveness of endovascular brachytherapy with iodine-125 (I-125) seeds strand for the treatment of extensive portal vein tumor thrombus (PVTT) in hepatocellular carcinoma (HCC) patients. Methods: A total of 40 HCC patients complicated by extensive PVTT who received I-125 seeds strand implantation from January 2015 to December 2022 at the Affiliated Zhongda Hospital of Southeast University were analyzed retrospectively. Endpoints included technical success rate, concurrent therapies, overall survival time and complications. Treatment of intrahepatic parts of HCC were also collected. Multivariate and subgroup analyses were conducted for overall survival. Results: The successful rate of operation was 100%, and there was no operation-related death. 37 patients received single I-125 seeds strand implant and 3 patients received double I-125 seeds strands. There is no active treatment of intrahepatic parts of HCC. TACE for intrahepatic tumor was performed in 16 patients (1 time in 14 cases, 2 times in 1 case, and 3 times in 1 case). 15 cases received a concurrent systematic therapies, in whom, two patients took the target drug less than 1 month. At a median follow-up of 3.5 (IQR, 2~8.5) months, the median overall survival (OS) of all patients was 92 days (95% CI: 77~108). The median OS was 128 days (95% CI: 101~155 days) in the I-125 seeds strand implantation plus systematic treatment group and was longer than that (75 days (95% CI: 36~114) of the I-125 seeds strand alone group (p = 0.037). Multivariate analysis revealed that without systematic treatment were independent risk factors affecting the prognosis in this study. Six patients died of upper gastrointestinal bleeding: four patients in the I-125 seed strand alone group and two patients in the combination of I-125 seed strand with systematic treatment group. Conclusions: The study shows that endovascular brachytherapy with I-125 seeds strand implantation is a safe and effective treatment method for extensive PVTT in HCC patients. The combination of I-125 seeds strand implantation and systematic treatment can prolong the survival time.